Evaluation of the microhaplotype markers in kinship analysis. Issue 7 (4th January 2019) - Zhu, Jing; Chen, Peng; Qu, Shengqiu; Wang, Yinji; Jian, Hui; Cao, Shuqiang; Liu, Yuqing; Zhang, Ranran; Lv, Meili; Liang, Weibo; Zhang, Lin
Abstract: Microhaplotype markers are emerging forensic genetic markers, which may supplement existing markers. Consisting of two to four SNPs with an extent of <200 bp, microhaplotype can be genotyped through massively parallel sequencing technology. Articles that have been published suggested that microhaplotype markers have good application prospect in forensics. Multiallelic haplotype loci are potentially important in certain forensic works, as the stutter and high mutation rate of short tandem repeats and the low polymorphism of single nucleotide polymorphisms may limit the power of these two kind of regular markers. In this study, we explored the potential of 11 new microhaplotype loci in kinship analysis. The results suggested that these loci have relatively high polymorphic information in different populations worldwide and relatively high system effectiveness in the kinship analysis. Microhaplotypes have potential for forensic kinshipg analysis.